Determination of "glyphosate" herbicide in some water sources in Latakia Governorate after oxidation to orthophosphate - الخير معروف; رسلان نور (Latakia University Journal -Medical Sciences Series, 2021)
glyphosate is the most widely used herbicide worldwide due to its low cost and unmatched ability to harm weeds. In 2015, the International Agency for Research on Cancer classified glyphosate in Group 2A as ’probably carcinogenic.’ This was based on “sufficient” evidence of cancer in experimental animals and “limited” evidence of cancer in humans. As a result of the above, and the fact that glyphosate is used in our region in uncontrolled methods, it was necessary to determine its concentrations in the environment. This research aims to determine glyphosate concentrations in some water sources in Latakia Governorate by applying a colorimetric method that uses Mo (V) -Mo (VI) reagent. The study included 48 samples from several shallow and deep wells and a river in Lattakia – Syria. When comparing the measured concentrations in the study with the international reference values, it was observed that all of them were within the limits permitted by the Environmental Protection Agency (700 μg/l in drinking water and 1800 μg/l for the protection of aquatic life) and the Canadian Ministry of Environment (280 μg/l in drinking water and μg/l and 800 for the protection of aquatic life), while they exceeded the limits permitted in the European Union (0.1 g/l in drinking water) and when comparing the concentrations measured in our study with those of reference studies it was observed that the concentrations in our study were higher than most of the other studies. Glyphosate concentrations were the highest in shallow-well samples (11.58-72.41) μg/l, followed by river samples (6.59-48.25) μg/l and then deep-well samples(2.46-23.56) μg/l. Overall, the concentrations peaked in the spring and summer seasons.